Promoting Resilience in Early Childhood Education and Care to Prepare Children for a World of Change: A Critical Analysis of National and International Policy Documents - Ann-Christin Furu; Angel Chan; Jonna Larsson; Ingrid Engdahl; Sarah Klaus; Anna May Navarrete; Barbara Turk Niskač (MDPI AG, 2023)
In recent years, the sustainability crisis has raised interest in the concept of resilience, i.e., the capacity to persist, adapt, or transform in the face of change and challenge. However, to date, resilience has only been studied to a limited extent within early childhood education and care (ECEC). This paper reports on a study that used critical document analysis of national and international policies to explore if and how the concept of resilience within ECEC could contribute to sustainability in a world of rapid change. Five national and four international documents were analysed through the theoretical lenses of childism and place-based education. The results show that resilience is implicitly expressed in ECEC policies yet is rarely linked to sustainability issues. Instead, policies mainly limit resilience to the psychological dimension and the individual child. The conclusion is that ECEC is an apt context for supporting resilience in multiple ways. It suggests using a holistic understanding of resilience to advocate for ECEC policies that include diverse perspectives of families and local communities, incorporate indigenous voices, and recognise the interconnectedness between humans and the more-than-human world.